Uso de hábitat en Fulica armillata, Fulica leucoptera y Gallinula chloropus durante la primavera - Heimsath, S.F. (1993)
In this paper we analyze the differences in hábitat use among Fulica armillata, F. leucoptera and Gallinula chloropus during spring, in relation to their abundances and activities. This work was carried out in an artificial pond located in the Parque Natural y Reserva Ecologica Costanera Sur. G. chloropus mainly use the coastal zone and the totoral, while Fulica species are more frequent in open water. Both Fulica coots are associated in the use of open water zones during feeding and of muddy vegetated coastal zone during resting. They differ in the use of the totoral (F. armillata doesn't use it), and emergent vegetation for rest. We discuss the differences exhibited by these species through analysis of morphology, behavior and ecological segregation.